Effect of lactation on postpartum pelvic floor muscle regeneration in preclinical model - F. Boscolo Sesillo; H. Manoochehri; P. Duran; E. Zelus; K. L. Christman; M. Alperin (npj Women's Health)
Abstract Pelvic floor muscle (PFM) recovery following childbirth is essential for preserving pelvic floor function. Despite this, the impact of parturition and lactation on pelvic muscle stem cells (MuSCs), indispensable for skeletal muscle maintenance and regeneration, remains unknown. We determined that vaginal delivery does not cause mechanical injury of the rat PFMs, enabling us to uncouple the effects of lactation on muscle homeostasis from PFM regeneration following simulated birth injury (SBI). Tibialis anterior (TA) served as non-pelvic control. This novel study demonstrates that in the absence of birth injury, lactation blocks MuSC proliferation in PFM and TA, suggesting that postpartum systemic milieu affects MuSCs in pelvic and non-pelvic muscles. In contrast, SBI negated the inhibitory effect of lactation on MuSCs in PFM but not in TA, indicating that local signals released by the injured muscle overcome systemic inhibitory effects of lactation, which persist in muscles remote from the site of injury.